Study of public approach towards COVID-19 vaccine doses - Sarkar, Jaimini; Sarkar, Chiradeep (Faculty of Medicine, 2025)
Vaccine hesitancy was one of India's problems after the COVID-19 vaccine roll-out. Earlier studies carried out to understand people's perception of the vaccine were mainly based on online or offline community-based surveys. These studies do not help to understand the actions taken by people towards vaccination. Hence, this study has been designed to understand the exact behaviour of people toward the vaccine Age-wise, the population was sub-grouped into three groups, above 18 years, 12-14 years, and 15-18 years. The data analysis has been done using cumulative coverage of vaccines in the said age groups The study shows a substantial population has missed second and booster doses of vaccine at the state, regional, and national levels in all three age groups. Even for the states that have shown the smallest number of people who missed their dose, their numb er is in the thousands Further research is needed to know, in total population, how many people have not even taken a single dose of vaccine. Policy-level efforts are needed to cover the country's entire population for at least a single dose and vulnerable populations, for additional booster doses after primary doses